EMPOWERMENT OF DALIT WOMEN AN ANALYSIS OF DALIT MOVEMENTS OF KERALA - VINUKUMAR N V (Human Rights International Research Journal, 2016)
In Kerala, paradoxically, social justice with economic growth or growth with equity has been the basic objective of public policy, with emphasis on reduction of exclusion. Before and since the formation of state dalit women also face the exclusion or marginalization from main stream society. Dalit women in Kerala faces social exclusion, land alienation, marginalization, poverty, lack of education, exploitation etc. In case of dalit women they are marginalized in to two senses; firstly they are dalit and secondly they are women. So there should be the need for empowerment of the dalit women. In Kerala before and after the formation of state various movements organized for the upliftment of the dalit community. Each and every dalit movement contributes to create the dalit identity, but this identity also without the power. So they are also always struggle for existence. This paper analyses and explores empowerment of dalit women and dalit movements in Kerala.